2005
DOI: 10.1016/j.visres.2005.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Glass-pattern detection is tuned for stereo-depth

Abstract: We investigated the role of disparity information in the detection of global form. Glass patterns, which allow insight into processing at both local and global stages of form analysis, were used as stimuli. We determined how detection of concentric Glass patterns is affected by a disparity difference introduced between partner dots forming local dipoles (Experiment 1), and how detection is affected by the addition of randomly oriented dot-pairs (noise dots) at crossed and uncrossed disparities (Experiment 2). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…Finally, our observations suggest that contour grouping in depth might involve the linking of a number of depth selective mechanisms that are tuned for a range of binocular disparities. This is similar to Hess and Field (1995),and to Khuu and Hayes (2005), who showed that the integration of local orientations occurs over large depth separations in the perception of global form in Glass patterns.…”
Section: Resultssupporting
confidence: 86%
“…Finally, our observations suggest that contour grouping in depth might involve the linking of a number of depth selective mechanisms that are tuned for a range of binocular disparities. This is similar to Hess and Field (1995),and to Khuu and Hayes (2005), who showed that the integration of local orientations occurs over large depth separations in the perception of global form in Glass patterns.…”
Section: Resultssupporting
confidence: 86%
“…[ 29 , 31 , 34 ]) by changing the ratio between dipoles oriented in the pattern direction (signal dipoles), and those that have random orientations, until the global structure can be just detected ( Fig 1B ). Typically Glass detection thresholds are 15–25% signal [ 27 , 38 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…Glass patterns (after Glass, 1969) are random dot stimuli consisting of dot-pairs with the same polarity (dipoles) configured to convey global structure (e.g., concentric structure in Figure 1B ). Glass patterns are particularly useful because their analysis by the visual system is well understood (e.g., Gallant et al, 1996; Bair et al, 2002), and reflects both local and global levels of computation: the orientation of local dipoles is initially extracted, and then combined at a later stage where the global form of the pattern can be determined (e.g., Wilson and Wilkinson, 1998; MacGraw et al, 2004; Wilson et al, 2004; Khuu and Hayes, 2005; Khuu et al, 2011). Thus, Glass pattern stimuli are ideal for investigating the processing of global form as they provide a direct probe of the mechanisms responsible for form integration that is not driven by top down influences unlike previously used stimuli (mentioned above) such as illusory contours and faces.…”
Section: Introductionmentioning
confidence: 99%